2021
DOI: 10.21834/jabs.v6i18.383
|View full text |Cite
|
Sign up to set email alerts
|

Neighborhood Park Visit Impacted Psychological Health in Reducing Stress

Abstract: This study examines the relationship between residents' stress levels with their participation at the neighborhood park in Petaling Jaya. The information on stress level and neighborhood park usage pattern proceed by distributing a questionnaire survey set. The outcome of this study identifies the connection of stress result with the usage pattern at the neighborhood park. Future research is recommended to have more than one case study with different demographic pattern backgrounds to enhance the residents' me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…According to Astell-Burt and Feng (2019), the study showed the number of tree canopies in a radius of 1.6km within the residential area is less prevalent in mental health. Open green spaces such as neighbourhood parks have a connection to the stress result with the appropriate elements such as safety (Hussein et al, 2021). Similar to Ishak et al (2018) highlighted design and accessibility, landscape elements, and safety as factors that contribute to the efficacy of alleviating stress in the community.…”
Section: Introductionmentioning
confidence: 96%
“…According to Astell-Burt and Feng (2019), the study showed the number of tree canopies in a radius of 1.6km within the residential area is less prevalent in mental health. Open green spaces such as neighbourhood parks have a connection to the stress result with the appropriate elements such as safety (Hussein et al, 2021). Similar to Ishak et al (2018) highlighted design and accessibility, landscape elements, and safety as factors that contribute to the efficacy of alleviating stress in the community.…”
Section: Introductionmentioning
confidence: 96%
“…This hardship prevents people from catering to basic needs and means they may have difficulty caring for themselves. A study undertaken by Hussein et al (2021) shows that spending time regularly in a natural setting can alter mental health and support a more positive and healthier lifestyle. Due to shortage of time, safety problems, and being able only to visit the park alone, there is often low interest among visitors to undertake park activities.…”
Section: Introductionmentioning
confidence: 99%
“…A number of these problems: feeling anxious and worried (59%); difficulty sleeping (50%); difficulty thinking (50%); tired all the time (50%); and had thoughts of ending one's life (9%) (Mirzaei-Alavijeh et al, 2017). Psychological health includes reducing stress, improving mood, and improving cognitive functions such as attention, concentration, memory, and others (Hussein et al, 2021). Creation sports are even more important to be applied by students and all their physical health benefits.…”
Section: Introductionmentioning
confidence: 99%